2016
DOI: 10.1007/s40271-016-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Applicability of the Disabilities of the Arm, Shoulder and Hand (DASH) Questionnaire to Patients with Hand Injuries and Diseases Using Rasch Analysis

Abstract: The study reveals that some DASH items do not fit the underlying trait that the DASH aims to measure. Further studies using Rasch analysis are needed to compare our findings with results of studies involving other target groups (e.g. patients with injuries of the upper arm and shoulder).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Consistent with our findings, DASH has been reported to violate the requirement of local item independence. A pattern of high residual correlation similar to ours where activity-related item group together while impairment-related items group together has been reported in patients with various upper extremity musculoskeletal disorders [ 15 , 16 , 18 , 34 , 36 , 37 ]. Similar to the approach used in the current study, Prodinger et al reported the use of two testlets (activity limitation and impairment testlets) to accommodate the issue of local dependency within the scale and this method yielded satisfactory fit to the Rasch model in line with the findings of the current study [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with our findings, DASH has been reported to violate the requirement of local item independence. A pattern of high residual correlation similar to ours where activity-related item group together while impairment-related items group together has been reported in patients with various upper extremity musculoskeletal disorders [ 15 , 16 , 18 , 34 , 36 , 37 ]. Similar to the approach used in the current study, Prodinger et al reported the use of two testlets (activity limitation and impairment testlets) to accommodate the issue of local dependency within the scale and this method yielded satisfactory fit to the Rasch model in line with the findings of the current study [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…Braitmayer et al reported poor discrimination for patients with low disability when analysing the DASH with a similar study population. 12 Forget et al also found that the DASH had better coverage and targeting in patients with high disability in a sample made up of Dupuytren's contracture patients. 7 The present patient sample represented a mixture of typical patients encountered at the hand surgery clinic (see Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…Studies that have used Rasch analysis on the DASH have shown several problems including multidimensionality of the data, disordered thresholds, differential item functioning (DIF) and high residual correlation between items. [12][13][14] Previously, to correct the problems of multidimensionality and local dependence, studies have removed items that do not fit the Rasch model 7,15 or split the DASH into subscales. 13,16,17 More recently, the creation of testlets has been proposed to solve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement invariance assesses the equivalence of items across specified groups, with only one study reporting no significant differences between group factors (sex, hand dominance, and side injured) and PEM score. 45 Braitmayer et al 15 conducted multifactor analysis for the DASH and reported DIF for sex. The Rasch-refined UEFI showed DIF for sex on 2 items “using tools/appliances” and “cleaning”.…”
Section: Discussionmentioning
confidence: 99%
“…The Rasch-refined UEFI showed DIF for sex on 2 items “using tools/appliances” and “cleaning”. 46 The PEM comprises symptom items (pain, stiffness, etc), whereas the DASH items with pronounced DIF were task based, specifically item 11 (carrying a heavy object) demonstrated important differences between sex, 15 which was mirrored by the task-based items with DIF in the UEFI. 46 The site-specific PROMs appraised here comprise some with mainly task-based items, some with symptom-based items, and some that are a mix of the 2.…”
Section: Discussionmentioning
confidence: 99%